Sistem Stok Baut Berbasis Desktop Pada PT. Ikoma Echo Robotech Indonesia - Hasidin; Muhtajuddin Danny; Asep Muhidin (Jurnal SIGMA, 2023)
Ikoma Echo Robotech Indonesia is a subsidiary of Ikoma Robotech Coorporation Japan which is engaged in robotics and system integration. In processing inventory data so far, it still uses a simple but computerized system, namely using Ms.Excel software, so that in calculating inventory, it experiences obstacles in the occurrence of errors in calculating the stock of goods in the warehouse. The method used by the author in this research is literature study by reading journals and data from the internet and field studies by taking data directly to PT. Ikoma Echo Robotech Indonesia. The result of this research is to produce an inventory information system that makes it easier for field, engineering and purchasing departments to provide reports to management and help minimize stock calculation error rates. In the inventory system, the author uses the VB application. Net, the report uses Microsoft Sql Server Management programming for data processing. After the researchers created an inventory information system, the authors hope that it can facilitate the work of the parties involved. Keywords: Robotic,VB Net,Stok System